Respiratory Syncytial Virus Disease Burden in Community-Dwelling and Long-Term Care Facility Older Adults in Europe and the United States: A Prospective Study. (1st March 2023) - Narejos Pérez, Sílvia; Ramón Torrell, Josep María; Põder, Airi; Leroux-Roels, Isabel; Pérez-Breva, Lina; Steenackers, Katie; Vandermeulen, Corinne; Meisalu, Sandra; McNally, Damien; Bowen, Jordan S T; Heer, Amardeep; Beltran Martinez, Adrian; et al.
Abstract: Background: Data on respiratory syncytial virus (RSV) disease burden in adults remain scarce. We assessed the burden of confirmed RSV-acute respiratory infections (cRSV-ARIs) in community-dwelling (CD) adults and those in long-term care facilities (LTCFs). Methods: In this prospective cohort study covering 2 RSV seasons (October 2019–March 2020 and October 2020–June 2021), RSV-ARIs were identified through active surveillance, in medically stable CD-adults ≥50 years (Europe) or adults ≥65 years in LTCFs (Europe and the United States). RSV infection was confirmed by polymerase chain reaction from combined nasal and throat swabs. Results: Of 1981 adults enrolled, 1251 adults in CD and 664 LTCFs (season 1) and 1223 adults in CD and 494 LTCFs (season 2) were included in the analyses. During season 1, overall incidence rates ([IRs] cases/1000 person-years) and attack rates (ARs) for cRSV-ARIs were 37.25 (95% confidence interval [CI], 22.62–61.35) and 1.84% in adults in CD and 47.85 (CI, 22.58–101.4) and 2.26% in adults in LTCFs. Complications occurred for 17.4% (CD) and 13.3% (LTCFs) of cRSV-ARIs. One cRSV-ARI occurred in season 2 (IR = 2.91 [CI, 0.40–20.97]; AR = 0.20%), without complications. No cRSV-ARIs led to hospitalization or death. Viral pathogens were codetected in ≤17.4% of cRSV-ARIs. Conclusions: RSV is an important cause of disease burden in adults in CD and LTCFs. Despite the observed low severity of cRSV-ARI, our results support the need for RSV prevention strategies among adults ≥50 years old. Abstract : In a prospective, multi-country, cohort study covering 2 consecutive RSV seasons (Oct2019/Mar2020, Oct2020/Jun2021), the incidence rate of confirmed RSV acute respiratory infections was 37.25 and 47.85 cases/1000 person-years in older adults in community-dwelling and long-term care facilities, respectively. Lay Summary: Lay Summary . Respiratory syncytial virus (RSV) causes respiratory illnesses, which can lead to serious complications in older adults. We estimated how common infections due to RSV are in adults living in the community or long-term care facilities (LTCFs). For 2 years, we observed approximately 2000 adults 50 years and older in Europe and the United States. Between October 2019 and March 2020, about 2 in 100 adults in this study had RSV infections; of these, fewer than one fifth had complications and there were no hospitalizations or deaths. Other viruses were present for less than one fifth of RSV infections. Between October 2020 and June 2021, during coronavirus disease 2019 (COVID-19) restrictions, we detected RSV infection in one adult, living in a LTCF, with no complications. RSV causes respiratory disease among adults 50 years and older, and therefore programs to prevent RSV infection are needed in this age group.